Scholarly investigation into otitis media: who is receiving funding support from the National Institutes of Health?. (13th February 2015) - Hojjat, Houmehr; Johnson, Andrew P.; Svider, Peter F.; Hong, Robert S.; Zuliani, Giancarlo; Folbe, Adam J.; Shkoukani, Mahdi A.
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis Otitis media (OM) is highly prevalent and represents a major public health concern. We evaluate National Institutes of Health (NIH) funding support for OM research and examine the role of otolaryngology primary investigators (PIs). Study Design Examination of bibliometrics and funding history of NIH grant recipients. Methods The NIH RePORTER database was examined for PIs funded for otitis media–related projects. The specialty, education level, academic department, scholarly impact (as measured by the h‐index), and funding levels of PIs were obtained. Results There were 320 projects funded for 1, 102 fiscal years supporting OM research. Since 2000, there has been >$280 million in support. PhDs received 47.5% of awards, more than any single medical specialty. Pediatricians received 54.8% of grants awarded to physicians followed by otolaryngologists (29.9%). Pediatric infectious disease specialists and pediatric otolaryngologists had the greatest funding per PI upon considering subspecialties, whereas non–fellowship‐trained otolaryngologists had the lowest funding levels. Funded otolaryngologists had lower scholarly impact than several specialties. Aggregate funding levels to otolaryngologists decreased between 2000 and 2013. Conclusions The NIH provided considerable grant support for researchers studying OM as awards to practitioners in numerous specialties exceeded a quarter of a billion dollars since 2000. Although awards to otolaryngologists were significant, the share of grants awarded to otolaryngologists has declined, suggesting that increased recruitment of basic scientists and enhanced cooperation with other specialists may facilitate further scholarship. These findings suggest a need for improving initiatives that prepare otolaryngology trainees interested in translational OM research for the rigorous NIH peer‐review grant process. Level of Evidence NA Laryngoscope, 125:1708–1714, 2015